The Effect Of Participative Decision-Making And Empowerment On Job Performance Of Engineers In Electric And Electronic Sectors - Kimpah, Jeniboy (2018)
The study examined the effect of participative decision-making, psychological empowerment, and environmental empowerment on in-role performance and creative performance. Furthermore, this research employed a matched-pair approach in examining the perspective of managers on their engineers’ in-role performance and creative performance. Two different sets of instruments had been distributed to the Malaysian Electric and Electronic manufacturing firms. A total of 173 matched-pairs questionnaires from 73 manufacturing firms was collected from managers and engineers in Johore, Selangor, Penang, Perak, and Sabah applicable to the analysis by using SPSS version 25 and SmartPLS version 3.2.7. The result revealed a positive and significant effect of participative decision-making on perceived meaning, perceived competence, perceived impact, work method, work schedule, and work criteria. Furthermore, the effect of perceived meaning, perceived competence, perceived impact, and work method on in-role performance was found to be positive and significant. In addition, the effect of perceived impact on in-role performance is also positive and significant. Mediation analysis was employed to test this research framework. The result of the mediation analysis demonstrated that perceived competence, perceived impact, and work method significantly mediate between participative decision-making and in-role performance. Another essential point is that the result revealed that perceived impact mediates between participative decision-making and creative performance.